China pluperfect. II, Practices of past and outside in Chinese art - Vigneron, Frank (Hong Kong : The Chinese University of Hong Kong Press, 2022)
"This book contains analysis of different domains of contemporary art in China seen through the lens of the epistemological changes described in China Pluperfect I: Epistemology of Past and Outside in Chinese Art.It first looks at the concept of "ink art," describing how it meant different things to different people in the former colony and how these different meanings came to determine certain institutional choices made at the beginning of the 21st century. The following chapters are dedicated to issues related to the urban and rural contexts for art creation in Mainland China and Hong Kong. One chapter observes the ups and downs of the representations of cities in the history of the People's Republic of China and how they have defined a certain idea of culture. Another looks at how Chinese cities have been exceptional centers of art creations over the last thirty to forty years through the example of Shenzhen where a vibrant art scene, albeit closely connected to Hong Kong which has become a major art hub in the last two decades, has developed. The following is dedicated to the changing fortunes of art making in the countryside, observing how institutions in the Mainland and in Hong Kong have supported these practices very differently.Frank Vigneron finally considers how the different speeds of globalization, slow in the past and fast today, have determined some of the issues of past and outside in the present, particularly in the context of socially engaged art in both the Mainland and Hong Kong."--Pulisher.
Introduction -- Chapter 1 Hong Kong Ink: A History of Past and Outside -- Bamboo Curtain and Mass Media -- Ink Society in Hong Kong -- Hong Kong Ink Art Museum -- Marginalization of Hong Kong Art -- Chapter 2 "When Is a Landscape Like a Body?" -- The Mollywood Series -- Mundane Mind and "Paintings of Beauties" -- Gender Positioning in Literati Culture -- Hong Kong Mundanity and Patriarchy in Mainland China -- Chapter 3 From Rural to Urban and Back Again -- Peace Reigns over the Riverin Hong Kong -- River of Wisdom in Shanghaiand Hong Kong -- Anti-urban Bias of the Maoist Period -- Pro-urban Bias of the 1990s and Beyond -- Chapter 4 New Urban Frontier -- "One Country, Two Systems,"and One Border -- The City over the Border: Shenzhen -- Three Plasticians in Shenzhen -- Art Market and Institutional Critique -- Chapter 5 New Rural Frontier -- Peasant Paintings duringthe Maoist Period -- "Beautiful Countryside" -- "Reviving the Countrythrough Culture" -- Socially-Engaged Art Practices in the Hong Kong Countryside -- Chapter 6 Multi-cultural World -- Past and Outside -- Mobility as Privilege -- Mobility as Necessity
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on March 01, 2023).
eBooks on EBSCOhost
Keywords: Art, Chinese -- Ming-Qing dynasties, 1368-1912.; History in art; Art and history -- China; Knowledge, Sociology of; Art criticism -- China -- History -- 18th century; Art criticism -- China -- History -- 19th century; Art criticism -- America -- History -- 18th century; Art criticism -- America -- History -- 19th century; Art chinois -- 1368-1912 (Dynasties des Ming et des Qing); Histoire dans l'art.; Art et histoire -- Chine; Sociologie de la connaissance; Critique d'art -- Chine -- Histoire -- 18e siècle.; Critique d'art -- Chine -- Histoire -- 19e siècle.; Critique d'art -- Amérique -- Histoire -- 18e siècle.; Critique d'art -- Amérique -- Histoire -- 19e siècle.; histories (visual works); sociology of knowledge; Art and history; Art, Chinese -- Ming-Qing dynasties; Art criticism; History in art; Knowledge, Sociology of; America; China; 1368-1912; History